Cachexia Versus Sarcopenia in Clinical Characteristics and Prognostic Value After Radical Gastrectomy for Gastric Cancer: A Large-Scale Prospective Study - Zhuang, Cheng-Le; Dong, Qian-Tong; Shi, Han-Ping; Zhang, Feng-Min; Luo, Xin; Wang, Wen-Bin; Yu, Zhen; Chen, Xiao-Lei; Wang, Su-Lin (Annals of surgical oncology, 2022)
Background Sarcopenia and cachexia are two predictors of adverse clinical outcomes, but they are partly overlapping. We aimed to compare the characteristics and prognostic value of cachexia and sarcopenia in patients after gastrectomy. Methods From 2014 to 2019, a total of 1215 gastric cancer patients were enrolled. Cachexia and sarcopenia were diagnosed according to the most recent consensus definitions. Baseline characteristics and clinical outcomes were compared between the two groups. Risk factors of survival were evaluated by Cox regression analysis. Results Of all patients, 26.5% were diagnosed with cachexia and 19.8% were diagnosed with sarcopenia. Sarcopenia was more prevalent in elderly patients, while cachexia was prone to occur in patients with TMN stage III. Survival curves showed that sarcopenia had adverse effects in patients with TMN stage I and II–III, while cachexia was only associated with poor survival at stages II–III. For the entire cohort, both cachexia and sarcopenia were adverse factors for prognosis. However, for stage I patients, sarcopenia was an independent predictor for overall survival (OS) (HR = 4.939, P < 0.001) and disease-free survival (DFS) (HR = 4.256, P < 0.001), but not cachexia; for stage II–III patients, cachexia was an independent predictor for OS (HR = 1.538, P < 0.001) and DFS (HR = 1.473, P = 0.001), but not sarcopenia. Conclusions Sarcopenia and cachexia have different clinical characteristics and prognostic values. For patients with early stage gastric cancer, detection for sarcopenia was more meaningful than cachexia. However, the prognostic significance of cachexia exceeded sarcopenia in advanced cancer.